A NEW 3D REACTOR MODEL FOR CRITICALITY SAFETY ANALYSIS OF NIRR-1 USING SCALE 6.2.3 - Salawa, Abdulhameed (FUDMA JOURNAL OF SCIENCES, 2020)
Detailed 3D model was developed for the Nigeria Research Reactor (NIRR-1) recently converted to 12.5% enriched UO2 core during the last quarter of 2018. The KENO3D module of SCALE 6.2.3 was used to visualize the geometry of the system before the criticality safety analysis was performed with the KENO-VI module of the code.  This model consists of over 10 different units that are properly placed at their exact position on the global unit. The coordinate of each fuel pin was calculated using the radius of the circle and the pin angular positions. Several reactor physics parameters generated include k-effective values by generation run, the average k-effective, the neutron lifetime, the generation time, the average number of neutron per fission in the system, the average energy group at which fission occurs, and the energy of the average lethargy causing fission in the system. Some of this information was used to determine how fast or thermal the spectrum of the modeled system was. A plot of average k-effective versus the number of generation run was used to determine whether the calculations performed using the input prepared for the modeled NIRR-1 system has source convergence difficulties or not.
Keywords: k-effective, neutronics, fission, absorption, thermal, leakage, control